Pengembangan Keterampilan Adaptabilitas Karyawan - Cindy Silvia Agustin; Tantria Desvi Vinata Sari; Puteri Aisyah; M. Isa Anshori (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Employee adaptability skills are increasingly important in a rapidly changing business environment. A recent literature review reveals the evolution of employees' adaptability skills during the COVID-19 pandemic and efforts to strengthen them. Factors such as leadership, changes in the work environment, and organizational support influence changes in adaptability. Inclusive leadership, open communication and social support form key elements in this strategy. This article describes the development of employee adaptability skills in the context of external change, especially the COVID-19 pandemic. This article describes material for developing employee adaptability skills which includes understanding the concept of adaptability, adaptability development strategies, and the benefits for companies and employees. This material is designed to help employees develop their abilities to deal with change, increase resilience, manage stress and innovate. By investing time and resources in developing adaptability skills, organizations can increase their competitiveness and employees can achieve success in a dynamic work environment. The results of this literature review provide useful insights for organizations that wish to prioritize developing employee adaptability in response to increasingly complex business dynamics.